Dimensión subjetiva de la convivencia: necesidad de una nueva lectura (Educational Perspectives Magazine (REPED), 2023)
In the last decades, Chilean society has experienced a series of changes that have caused variation in the physiognomy of its relationships and have modified its interpretative referents. Today, there are new ways of perceiving ourselves and of perceiving the coexistence of our identities. This paper discusses the need to express these representations in the students who want to become teachers.
Keywords: Coexistence, Modemity, Collective Historical Sense, Imaginaries, Education, Citizenship.